ETHNOMEDICINE OF BAJO TRIBE COMMUNITY IN BANGKO VILLAGE, MAGINTI DISTRICT, WEST MUNA, SOUTHEAST SULAWESI - Fachruddin Fachruddin; Musthamin Balumbi; Dustan Dustan (Universitas Medan Area, 2021)
This study aims to reveal the use of marine and coastal plants, and animals as medicine by Bajo Tribe society in Bangko Village, West Muna. The method used was an exploratory survey. Data were collected using in-depth interviews with 20 traditional healers selected by purposive sampling. The data obtained were analyzed descriptively. The result revealed that there were 39 species of plants and 5 species of animals used as medicine. The most widely used plant families were the Arecaceae and Poaceae, 3 species respectively, while animals from the families of Holothuriidae, Onuphidae, Pinnidae, Syngnathidae, and Tridacnidae, 1 species respectively. The most commonly part of plant used was leaves (50%), while for animal was parts of flesh and whole body were used 40% respectively. The most commonly used preparation and application were boiling and drinking. In conclusion, Bajo people in Bangko Village with their maritime culture use plants and animals in the marine and coastal environment to overcome various diseases and health problems, in addition using “baca-baca” method.